Iberische Halbinsel. Die Terrakotten der Iberischen Halbinsel von den vorgeschichtlichen Anfängen bis zum Ausgang der Antike - Marzoli, Dirce (e-Forschungsberichte des DAI, 2017)
The project “The Terracottes of the Iberian Peninsula” has set out the documentation and commentary of all the terracotta types of this subcontinent from the Late Bronze-Age to the Late Antiquity in the form of a commented catalogue. It thus encompasses the types of the Phoenician-Punic, the Greek, Proto-historical and Roman terracottes and their respective problems, especially their different influences and interpretations. The structuring of this material was developed on the basis of the most extensive group of Roman terracottes. The work on the Greek terracottes was completed in 2014, on the Roman 2016, on the Iberian and Celt-Iberian terracottes in 2017.